Road Lights Profiling Based on Road Lighting Setting-Up and Performances - Prasetijo, J.; Mohd Nar, M.A.; Mohd Jawi, Z.; Ngadiron, Z.; Mahyeddin, M.E.; Norrizan, M.; Abd Latif, M.F. (Journal of the Society of Automotive Engineers Malaysia, 2021)
Roads and highways are the areas where road accidents commonly occurred, and the number increases during a certain period such as festive breaks. ASEAN NCAP is committed to ensuring the safety of vehicles in Southeast Asia by improving the rating systems and standards of a vehicle such as AEB and AHB. Additionally, efforts on the improvements of street/road lighting performances and facilities (profiling and design) would play an important role in safety along the road stretches since vehicle lighting are strongly correlated with visual effectiveness. Road lighting performance with low hence and low visual quality would contribute to accidents in certain road sections. Therefore, this study experimented with road lighting performance environments by using Luxmeter based on the Euro NCAP (2018) standard and guideline. A reference grid of road light measurement with a 1-meter interval was used to measure lighting performance on each distance interval. Two federal roads in Johor were picked as experiment sites, i.e. FT050 (Jalan Batu Pahat – Ayer Hitam – Kluang) and FT001 (Jalan Johor Bahru – Segamat). FT050 road is a two carriageway with a width average of 2.6 meters, 134- kilometer in length, and the lamp used most was a double arm lamp. FT001 is similar in width (2.6-meter), 992.6-kilometer in length, and used single- arm lamps. The study found that FT050’s lighting performance decreasing at each interval grid while away from the lights at the range of 38 lux to 16 lux, however, FT001’s result was decreasing at mid-interval and it increases when approaching mid between the lights at 23 lux – 15 lux – 19 lux. The following study concluded that using single arm lighting systems (by turns) resulting in higher lights (lux) performances and larger (lux) distributions (coverage) on roads. Therefore, the installments of single arm lighting system (by turns) would be considered for lights performance and efficiency concerning the drivers’ visibility.